1992
DOI: 10.2307/2532307
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Assessment of Saddlepoint Approximations for Testing a Logistic Regression Parameter

Abstract: Saddlepoint methods provide quick and easy approximations to significance levels for conditional tests of logistic regression parameters. We evaluate the accuracies of saddlepoint approximations for three well-known conditional tests: Bartlett's test for no three-factor interaction in a 2 x 2 x 2 table, the test for trend in a series of probabilities, and the exact test of no association in stratified 2 x 2 tables with a common odds ratio. General recommendations are suggested regarding the use of saddlepoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Some real examples of other sorts of small data sets are given in Reference [1]. Inference based on large sample results can be highly inaccurate when applied to small samples, particularly when data are imbalanced or nearly separated [2]; saddlepoint and Edgeworth approximations can signiÿcantly improve inference [3,4]. However, if a hyperplane can be found that separates the independent variables for one outcome from those for the alternative outcome, logistic regression procedures will fail to converge, and maximum likelihood estimates (MLEs) for the regression parameters will tend to ±∞.…”
Section: Introductionmentioning
confidence: 99%
“…Some real examples of other sorts of small data sets are given in Reference [1]. Inference based on large sample results can be highly inaccurate when applied to small samples, particularly when data are imbalanced or nearly separated [2]; saddlepoint and Edgeworth approximations can signiÿcantly improve inference [3,4]. However, if a hyperplane can be found that separates the independent variables for one outcome from those for the alternative outcome, logistic regression procedures will fail to converge, and maximum likelihood estimates (MLEs) for the regression parameters will tend to ±∞.…”
Section: Introductionmentioning
confidence: 99%
“…Although it would be simpler to illustrate the methods for continuous data, we feel that much of the important practical use of these methods, for exponential families, will be for discrete data. Davison (1988) and Bedrick and Hill (1992) consider applications much the same as here.…”
Section: Introductionmentioning
confidence: 99%
“…This can also happen when the table is small but contains very large as well as small cell counts. For such problematic tables, there should be additional research on (1) hybrid algorithms that use exact methods for some parts of the computation and approximations for other parts (Baglivo, Olivier and Pagano, 1988), (2) fast ways of simulating the exact distribution (Kreiner, 1987;Mehta, Patel and Senchaudhuri, 1988), and (3) better asymptotic approximations (e.g., Koehler, 1986), including saddlepoint approximations (Davison, 1988;Booth and Butler, 1990;Bedrick and Hill, 1992;Pierce and Peters, 1992).…”
Section: Future Researchmentioning
confidence: 99%